A química dos plásticos: impactos e conscientização na educação básica - Will, Giseli (2024)
In chemistry teaching, the aim is to mediate the learning of concepts and theories, using students' previous knowledge as a basis for developing scientific knowledge, giving it concreteness and intelligibility. The use of synthetic polymers, especially plastic materials, is very important in this context because, as they are part of everyday life, these materials permeate students' knowledge and make it possible to contextualize various contents. In addition, these materials have properties such as Iightness, water resistance and malleability, which are indispensable in contemporary life. However, excessive consumption and improper disposal result in serious environmental problems, since they require a long time to degrade in nature. Thus, this research aims to identify what contributions a didactic practice using recyclable plastics, to be carried out with students from two secondary school classes in a state school in the municipality of São Mateus-ES, can bring to the understanding of chemistry content and to the development of environmental awareness about the impacts caused by the inappropriate disposal of these materials. To this end, the methodology of this research is based on a qualitative analysis, initially of an exploratory nature, through the application of a questionnaire, analyzed mainly through the method of descriptive statistical analysis, then with the execution of a Didactic Sequence, described and analyzed through the reports of the researcher's Iogbook, and finally with a semi-structured interview, analyzed through the method of content analysis proposed by Bardin (2011). The results indicated that, after the Didactic Sequence, the participants began to better understand the different types of plastics and their environmental impacts, as well as establishing connections between the chemistry content and its use in everyday life. In short, the didactic practice was effective in broadening the students' knowledge and promoting critical awareness of the importance of recycling and the proper disposal of plastic materials.